ERP conceptual ecology - Bento, F.; Costa, C. J.; Aparicio, M. (Advances in Intelligent Systems and Computing, 2019)
The technological evolution of recent years has made that information systems frequently adapt to the market realities to fulfill the improvements of the company’s organizational processes. In this context, new paradigms, approaches, and concepts were disseminated through the new realities of information systems. This study aims to verify how ERP (Enterprise Resource Planning) has been related to other information systems within its ecosystem. For this purpose, we have reviewed the literature based on 650 publications whose central theme was the ERP. The data were treated through a graphical analysis, inspired by SNA (Social Network Analysis), represented by related ERP concepts. The study results, determine the connection degree between the concepts that emerged with the technological evolution and the ERP, thus representing the ERP interoperability tendencies, over the last years. The study concludes that ERPs have been improving and substantially increasing the conditions of interoperability with other information systems and with new organizational concepts that have emerged through the technological availability. This fact led to a better organizational process’s adoption and more organizational performance.